IDENTIFIKASI GOLONGAN SENYAWASITOTOKSIK TERHADAP SEL KANKER T47D EKSTRAK KLOROFORM DAUNPiperspp.KOLEKSI KEBUN RAYA BOGOR - , YUS HARGONO CAHYANING YUDI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Genus Piper has been using traditionally as medicines. Piper aborescen, P. crocatum, P. Imperiale, P. longum, and P. methysticum have ability to inhibit breast cancer proliferation. This research goal is to identify of cytotoxic compound group against T47D cancer cell from chloroform leaf extract of Piper spp. in Bogor Botanical Gardens. Cytotoxic activity determined by MTT assay for crude extract, fraction and isolate. Syringe reagents such are cerium (IV) sulphate, lieberman-burchard, vanillin sulphate, sitroborat, dragendorf and ammonium vapor to identify their bioactive compound group. The result showed that chloroform extract of P. porphyrophyllum has highest recovery extract (19.5%), most variety chromatogram (at least 10 compounds), highest content of chromophore groups and lowest IC50 (522.1 Î¼g/ml). Fraction group A has lowest IC50 (36.22 Î¼g/ml) but their cytotoxic decresing by further fraction (shown that has synergies compound) and minimum dose 200 Î¼g/ml could killed vero cell (normal cell) the rest 36.38%. Isolate V have potential active compounds (IC50 60.11 Î¼g/ml) inhibit T47D proliferation and selectve for vero cell. Major active compound of P. porphyrophyllum was terpene and alkaloids. It could be concluded that terpene and alkaloids form isolate V of P. porphyrophyllum are potential cytotoxic compound against breast cancer (IC50 60.11 Î¼g/ml) and selective for vero cell. Further research needed for group A fraction (IC50 36.22 Î¼g/ml) that killed vero cell on 200 Î¼g/ml.